Pembuatan Permen Susu Rasa Jahe di Kelompok Wanita Tani Kecamatan Batu Kota Batu - Finda Swastika Emas; Luki Amar Hendrawati; Ach Syamsudin (Politeknik Negeri Jember, 2018)
The making of Ginger Flavored Milk Candy was done because the Women Farmers Group (KWT) in Batu District needs products by utilizing the abundant potency of milk and ginger plants. The population of dairy cows in Batu District in 2017 was 4,475, have milk production of 385,710 liters / year. The production of ginger was 30-40 tons per year in an area of 3-4 hectares. The purpose of this study was to find out the results of making Ginger Flavored Milk Candy. The research method used was Kaji Widya. The ginger flavored milk candy that was compared was milk candy with ginger powder and crushed ginger. The analytical tool used was Organoleptic Test with the measured aspects including color, taste, aroma, and texture. The results of organoleptic tests showed that milk candy that uses ginger which was crushed was morepreferred by panelists. If KWT wants to make ginger milk candy as a product,then it is recommended to use crushed ginger.